2021
DOI: 10.1016/j.celrep.2021.109391
|View full text |Cite
|
Sign up to set email alerts
|

Antibody landscape against SARS-CoV-2 reveals significant differences between non-structural/accessory and structural proteins

Abstract: The immunogenicity of SARS-CoV-2 proteome is largely unknown, especially for non-structural proteins and accessory proteins. Here we collect 2,360 COVID-19 sera and 601 control sera. We analyze these sera on a protein microarray with 20 proteins of SARS-CoV-2, built an antibody response landscape for IgG and IgM. Non-structural proteins and accessory proteins NSP1, NSP7, NSP8, RdRp, ORF3b and ORF9b elicit prevalent IgG responses. The IgG patterns and dynamic of non-structural/ accessory proteins are different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 46 publications
(66 reference statements)
1
26
0
Order By: Relevance
“…Similarly, Lynch et al reported that the IgG and IgM levels against the RBD and N proteins were significantly higher in patients admitted to the intensive care units compared to those with a milder disease in all time intervals [ 17 ]. Li et al explored the IgG responses against various structural and non-structural SARS-CoV-2 antigens and found that the positivity rate and/or IgG levels against S1, NSP1, NSP7, NSP8, RdRp, ORF3b and ORF9b were significantly higher in patients with severe than non-severe disease [ 18 ]. From these non-structural proteins, only NSP1 and ORF3b were represented on our antigen array.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lynch et al reported that the IgG and IgM levels against the RBD and N proteins were significantly higher in patients admitted to the intensive care units compared to those with a milder disease in all time intervals [ 17 ]. Li et al explored the IgG responses against various structural and non-structural SARS-CoV-2 antigens and found that the positivity rate and/or IgG levels against S1, NSP1, NSP7, NSP8, RdRp, ORF3b and ORF9b were significantly higher in patients with severe than non-severe disease [ 18 ]. From these non-structural proteins, only NSP1 and ORF3b were represented on our antigen array.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be considered that additional SARS-CoV-2 antigens, different from the “classic” Spike, Nucleoprotein and Membrane may be of importance to track SARS-CoV-2-specific memory durability. This is further supported by the recent identification of antibodies against non-structural/accessory proteins in COVID-19 patients, as well as of HLA-I peptides derived from both canonical open reading frames (ORFs) and internal out-of-frame ORFs of S and N proteins [ 230 , 217 ]. These data open the way to further investigation and strategic approach in monitoring SARS-CoV-2 specific immune response.…”
Section: Heterogeneous Adaptive Immune Response To Sars-cov-2mentioning
confidence: 96%
“…To further confirm the applicability of the protein microarray, 14 convalescent sera (Table S1-cohort 1) were analyzed following an established protocol 6,7 , besides IgG, IgM and IgA responses were also compared between RBD-WT and RBD-Omicron. Significantly lower signals were observed for all these 3 types of antibodies against RBD-Omicron, specifically, 3.44x, 8.71 and 4.26x for IgG, IgM and IgA, respectively.…”
Section: The Omicron Rbd Protein Microarraymentioning
confidence: 99%